Development of an Arabic Version of the Hiroshima University- Dental Behavioral Inventory: Cross-cultural Adaptation, Reliability, and Validity - Dany Daou; Khaldoun Rifai; Bassel Doughan; Mounir Doumit (Springer, 2018)
The Hiroshima University-Dental Behavioral Inventory (HU-DBI) has not been adequately translated to the Arabic language. The aim of this study is the translation and cultural adaption of the English HU-DBI into standard Arabic. The English HU-DBI was translated into Arabic by three bilingual dental academics. A nonmedical professional performed backward translation into English. The three bilinguals compared both English versions and accordingly modified the Arabic version. English and Arabic versions were answered by 58 bilingual participants. Focus groups and cognitive interviews were conducted to pretest the working version, after which the final Arabic version was tested for test-retest validity on 58 dental students. Bilingual validity and test-retest validity were assessed using the kappa statistic. Responses were similar in the English and Arabic versions for bilingual individuals and on both tests in the test-retest sample. Kappa values ranged from 0.85 to 1.00 for bilingual validity and between 0.82 and 1.00 for test-retest reliability. In conclusion, the Arabic HU-DBI will enable the assessment of knowledge and attitudes toward oral diseases and their prevention in Arab countries and will allow meaningful comparisons between different countries in the region.